Extracellular polymeric substances (EPS) producing and oil degrading bacteria isolated from the northern Gulf of Mexico. - Hernando P Bacosa; Manoj Kamalanathan; Meng-Hsuen Chiu; Shih-Ming Tsai; Luni Sun; Jessica M Labonté; Kathleen A Schwehr; David Hala; Peter H Santschi; Wei-Chun Chin; Antonietta Quigg (PLoS ONE, 2018)
Sinking marine oil snow was found to be a major mechanism in the transport of spilled oil from the surface to the deep sea following the Deepwater Horizon (DwH) oil spill. Marine snow formation is primarily facilitated by extracellular polymeric substances (EPS), which are mainly composed of proteins and carbohydrates secreted by microorganisms. While numerous bacteria have been identified to degrade oil, there is a paucity of knowledge on bacteria that produce EPS in response to oil and Corexit exposure in the northern Gulf of Mexico (nGoM). In this study, we isolated bacteria from surface water of the nGoM that grow on oil or Corexit dispersant. Among the 100 strains isolated, nine were identified to produce remarkable amounts of EPS. 16S rRNA gene analysis revealed that six isolates (strains C1, C5, W10, W11, W14, W20) belong to the genus Alteromonas; the others were related to Thalassospira (C8), Aestuariibacter (C12), and Escherichia (W13a). The isolates preferably degraded alkanes (17-77%), over polycyclic aromatic hydrocarbons (0.90-23%). The EPS production was determined in the presence of a water accommodated fraction (WAF) of oil, a chemical enhanced WAF (CEWAF), Corexit, and control. The highest production of visible aggregates was found in Corexit followed by CEWAF, WAF, and control; indicating that Corexit generally enhanced EPS production. The addition of WAF and Corexit did not affect the carbohydrate content, but significantly increased the protein content of the EPS. On the average, WAF and CEWAF treatments had nine to ten times more proteins, and Corexit had five times higher than the control. Our results reveal that Alteromonas and Thalassospira, among the commonly reported bacteria following the DwH spill, produce protein rich EPS that could have crucial roles in oil degradation and marine snow formation. This study highlights the link between EPS production and bacterial oil-degrading capacity that should not be overlooked during spilled oil clearance.